Technology for Obtaining Functional Flour from Barley Grain - Sarbalaev Farrukhbek Nabievich; Bekmirzaev Shokhrukh Ikrom ugli; Jahangirova Gulnoza Zinatullayevna (Peerian Journals Publishing, 2023)
This article is devoted to the technology of obtaining functional flour from barley grain
Keywords: grain; flour; technology; production